The Ce3+ Metal Ion Adsorbent Based on Calcium Alginate Loaded Fe3O4 (Ca-Alg/Fe3O4) - Haili, Hulqi Mila; Rusnadi; Yulianti, Silmi Nur'asni (MultiTech Publisher, 2023)
Rare earth metal frequently utilized in technological advancements is cerium. The high utilization of cerium correlates with the depletion of primary REEs reserves and the accumulation of secondary materials that can enter aquatic environments. Recycling and recovery of REEs through methods such as solvent extraction, filtration, and adsorption are commonly employed. Adsorption is chosen due to the abundance of adsorbent materials in nature, simple fabrication, efficiency, and cost-effectiveness. Calcium alginate biosorbent loaded with magnetite (Ca-Alg/Fe3O4) has been used to adsorb (Ce3+)aq, with optimal conditions achieved at Ca-alginate:Fe3O4 ratio of 2:1 (w/w), 0.075 g, pH 4, a contact time of 210 minutes, and 250 ppm, [Ce3+]0. The adsorption process follows the Langmuir isotherm model with qmax at 50.505 mg/g. Hence, the Ca-Alg/Fe3O4 biosorbent shows potential in adsorbing (Ce3+)aq.